Pelatihan Dasar-Dasar Pengolahan Makanan Bagi Pelaku dan Pengelola Home Stay di Desa Tabola, Sidemen, Bali - putu eka trisdayanti; I Nyoman Sunada (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
This community service aims to provide training in basic food processing to tourism actors in Tabola Village, Sidemen, Karangasem. Based on the analysis of the situation and needs, it is known that tourism actors need to improve skills in processing food for their guests. To meet this need, a short training program on breakfast processing, sauce processing and its derivatives was designed and then implemented. The methods used in this training session are presentations on CHSE restaurants, menu knowledge, cooking demonstrations, and practices of the participants. The evaluation results showed that the participants were enthusiastic about participating in the training and were able to practice food processing methods.